Youth: The Right to a Place in the Sun - Gomes, Candido Alberto (2013)
Changing population patterns aggravated by the financial crisis unleashed in 2008 reveal altered population dynamics that include increased longevity, population ageing and an expanding moratorium on youth. As generations that are more markedly defined sociologically take shape, a population bulge of young people awaiting work opportunities and the chance to become productive adults has now formed that demonstrates revolutionary potential. The transformations underway are leading to a re-dimensioning of traditional intergenerational resource transfers and underscoring the vulnerability of the various generations, particularly the adult generation, which is under increased pressure. In this context, education appears to be a dead end in several countries, since it no longer functions as a means toward social ascension. The over-rated value of the diplomas being conferred has become apparent and contrasts sharply with societies that are actually dedicated to reducing jobs and making employment increasingly precarious. It is a crisis scenario in which the legitimacy of education is seriously being questioned.